Towards the intensity consistency of the ozone bands in the infrared range: Ab initio corrections to the S&MPO database. (September 2021) - Tyuterev, Vladimir; Barbe, Alain; Mikhailenko, Semen; Starikova, Evgeniya; Babikov, Yurii
Highlights: About 40% of intensities in the "Spectroscopy and molecular properties of Ozone" (S&MPO) information system were corrected using ab initio dipole moment functions in the 0 - 4122 cm −1 range for thirty cold and hot bands of the main ozone 16 O3 isotopologue. Abstract: Accurate knowledge of line parameters, and particularly line intensities is of primary importance for satellite, ground based and balloon measurements of the ozone concentration in the atmosphere. Self-consistency in absolute band intensities of ozone in various spectral intervals is necessary to avoid discrepancies in the atmospheric ozone retrieval from different windows. Difficulties in precise experimental characterization of absolute line intensities of this unstable molecule are well known leading to many significant deviations in published intensity values and in spectroscopic compilations. Ab initio intensities computed from the dipole moment functions of our previous works (Tyuterev et al. JCP 2017;146:064304; JCP 2019;150:184303) have permitted achieving a consistency between Stark-effect measurements and various databases in 10 and 5 µm in a good agreement with the most accurate recent experiments. In this paper we extend ab initio corrections to available line lists of ozone band intensities in wider IR range up to the bands with four vibrational quanta. About 40% of intensities were corrected in the 0 - 4122 cm −1 range for thirty cold and hot bands of the main ozone 16 O3 isotopologue. Most of them, but not all, were obtained using band specific scaling factors ranging from 0.75 to 1.17 making quite significant changes in the absolute values. The full line lists containing corrected line intensities in the spectral intervals considered in the paper are provided in the Supplementary material for this work. The resulting line list is now available on the web site of the "Spectroscopy and Molecular Properties of Ozone" (S&MPO) information system ( http://smpo.iao.ru ; http://smpo.univ-reims.fr ) . A large part of this line list including the ab initio correction reported in this work will be used in the future HITRAN20 update.